Planning support methods. Urban and regional analysis and projection. - Klosterman, Richard E.; Brooks, Kerry; Drucker, Joshua; Feser, Edward; Renski, Henry (Rowman & Littlefield, 2018)
Planning Support Methods offers a practical guide to the key methods of urban and regional planning. The authors apply and critically assess the most important methods for demographic and economic analysis and projection and land suitability analysis, providing an essential resource for practicing planners and planning students alike.
Keywords: Stadtplanung; Regionalplanung; Planungsmethode; Raumanalyse; Landnutzung; Modell; Mathematik; Methode; Quantifizierung; Trend; Projektion; Demographie; Lokale Ökonomie; Lehrbuch